A MODERN SOLUTION FOR METROLOGICAL PROVISION OF "DIGITAL NIVERLIR – BARCODE RAIL" MEASUREMENT SYSTEMS - Suyunov A. S.; Mirzaev A. A.; Suyunov S. A.; Tukhtamishev S. S. (Western European Studies, 2024)
The article covers issues related to metrological maintenance and research of geodetic instruments used in leveling. The methods of checking the main metrological parameters of the barcodes of the digital levels and the methods of checking the technological schemes of the barcodes are compared. Determining the deviation of the average length of the bar meter from the nominal value is carried out twice a year, before the beginning of the field season and after its end, using autocollimators. In the article, methods of solving this problem, implemented in field conditions using various methods, were presented.
Keywords: verification; calibration; digital level; barcode staff